The Effect Of Independence and Work Schedule On Employee Performance and Job Satisfaction In The Department Agriculture, Marine and Fisheries Parepare City - Parman Parman (Economos : Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine 1) The Effect of Independence on Employee Performance, 2) The Effect of Work Schedule on Employee Performance, 3) The Effect of Independence on Job Satisfaction, 4) The Effect of Work Schedule on Job Satisfaction, 5) The Effect of Independence on Employee Performance and Job Satisfaction 6) The Effect of Work Schedule on Employee Performance and Job Satisfaction . The data collection techniques used are Observation and Questionnaire Division. The population in this study was all employees who worked in the Agriculture, Marine and Fisheries Service of Parepare City which amounted to 107 respondents. The analysis technique used is the SEM-PLS (Structural Equation Modelling-Partial Least Square) analysis technique using the WarpPLS 7.0 application. Theresearch objectives are 1) Independence does not have a Significant effect on Employee Performance, 2) Work Schedule Has a significant effect on Employee Performance, 3) Independence has a significant effect on Job Satisfaction, 4) Work Schedule has a Significant effect on Job Satisfaction, 5) Independence does not have a significant effect on employee performance and is not mediated by Job Satisfaction, 6) Work Schedule on Performance has a significant effect on Performance and is mediated by job satisfaction and experiences partial or partial mediation.